The future role of metal-on-metal hip resurfacing. - Matharu, G; Pandit, H; Murray, D; Treacy, R (Springer Berlin Heidelberg, 2015)
PURPOSE: The purpose of this review was to assess the ten to 15-year outcomes of metal-on-metal hip resurfacing (MoM HR) when performed at designing and independent centres, and make recommendations for the future use of MoM HR. METHODS: Studies reporting ten to 15-year outcomes for modern MoM HR devices from both designing and independent centres were reviewed. Outcomes from these studies were assessed to allow the formulation of recommendations for the future use of MoM HR. RESULTS: Two MoM HR designs, the Birmingham Hip Resurfacing (BHR) and Conserve Plus, have outcomes reported at a minimum of ten years. The BHR was the only device with outcomes reported at a minimum of ten years by both designing (overall survival of up to 95.8 % at 15 years) and independent surgeons (overall survival of 87.1-94.5 % at ten years). Implant survival in these seven BHR studies was influenced by the pre-operative diagnosis (primary osteoarthritis had better outcomes), gender (male patients had better outcomes), and femoral component head size (larger sizes had better outcomes). In contrast to independent centres, designing surgeons reported acceptable outcomes in female patients undergoing BHR. CONCLUSIONS: There remains a role for MoM HR in young active male patients with primary osteoarthritis, provided the surgeon has sufficient experience in the procedure, the implant has an established record, and the patient is aware of the potential risks associated with MoM bearings and HR. Very experienced HR surgeons may also consider this procedure in females provided they meet the refined inclusion criteria described (including femoral head sizes of 46 mm and above).